Resin glue solution, preparation method of resin glue solution and method for manufacturing film-free flexible copper-clad plate by using resin glue solution
A resin adhesive composition directly applied to copper foil addresses the limitations of existing methods by enhancing heat resistance, bending resistance, and peel strength in flexible copper clad laminates, reducing costs and labor intensity.
Patent Information
- Application Number
- CN202411732548.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing methods for producing flexible copper clad laminates are costly, labor-intensive, and result in products with poor heat resistance and bending resistance, particularly those using film-based adhesives like nitrile rubber.
A resin adhesive composition comprising phenolic resin, epoxy resin, flexible materials, flame retardants, and fillers is directly applied to copper foil, followed by a specific preparation and curing process to create a film-free flexible copper clad laminate with high heat resistance, bending resistance, and peel strength.
The method reduces costs, improves heat resistance, bending resistance, and peel strength, eliminating the need for films and lowering labor intensity while achieving superior performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of printed circuit boards, and relates to a flexible copper-clad laminate and a special resin adhesive for the flexible copper-clad laminate, and in particular to the resin adhesive, a method for preparing the resin adhesive, and a method for making a film-free flexible copper-clad laminate using the resin adhesive. Background Art
[0002] Flexible copper clad laminate (FCCL) refers to a copper clad laminate formed by bonding copper foil to one or both sides of a flexible insulating material such as polyester film or polyimide film by coating adhesive. Flexible copper clad laminate is widely used in aerospace equipment, navigation equipment, aircraft instruments, military guidance systems, and electronic products such as mobile phones, digital cameras, digital video cameras, automotive satellite positioning devices, LCD TVs, and laptops. With the development of the times, it will also be widely used in artificial intelligence robots, smart wearables, unmanned driving, and other 5G and Internet of Everything aspects.
[0003] At present, there are two methods for making flexible copper clad laminates: one is the lamination method, which uses the cured PI film to apply thermoplastic PI glue, and directly uses copper foil to press and cure. This method of PI glue and coating method is currently only produced in Japan and the United States. The price is high and the materials are limited. Its flexible copper clad laminate has excellent performance and is used in high-end products; the other is the coating method, which applies adhesive (the main component is nitrile rubber) on the PI film, dries it in an oven, and then covers it with copper foil for pressing and curing. This method has poor heat resistance and bending resistance, and has many steps and high labor intensity.
[0004] The invention is to directly apply it on the copper foil without using a film, and allow the glue to solidify to automatically generate a high heat-resistant, high bending-resistant, and high-peeling flexible board. It can not only replace the pressed product, but also has low cost and reduces the labor intensity of personnel. Summary of the invention
[0005] In view of the above problems, the present invention proposes a new production method, which is embodied in the invention of the glue formula. The integrity of the glue formula is ultimately to embody self-filming, high heat resistance, high bending resistance, and high peel strength; secondly, it is directly coated on the copper foil to finally obtain a flexible copper clad laminate.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is a resin glue solution, characterized in that it specifically comprises, in parts by weight: 100-190 parts of phenolic resin; Epoxy resin 30-60 parts; 80-150 parts of flexible materials; Flame retardant 20-40 parts; 20-40 parts of filler; Solvent A 500-1000 parts; The phenolic resin is a thermosetting phenolic resin, which specifically includes, by mass fraction: Phenol 110-130 parts; 150-160 parts of formaldehyde solution; 15-25 parts of triethylamine; Solvent B 260-360 parts; The preparation method of the phenolic resin is: a. subjecting a certain mass fraction of phenol, formaldehyde solution and triethylamine to polymerization reaction, the reaction temperature is 80-100°C, and the reaction time is 30-60min; b. Then vacuum dehydration, the processing time is 90-100min, and the dehydration amount is 95-105 parts; c. Add solvent B to cool and dissolve, and obtain a phenolic resin solution with a solid content of 52-55%, that is, the phenolic resin in the resin glue. The solvent B is a mixture of one or more solvents selected from the group consisting of methanol, ethanol, ethylene glycol monomethyl ether, acetone and butanone.
[0007] Preferably, the solid content of the formaldehyde solution is 36%-38%.
[0008] Preferably, the epoxy resin is one or more low molecular weight epoxies with an epoxy equivalent of 160-200 g / eq, and the best structures are bisphenol A type and bisphenol F type.
[0009] Preferably, the flexible material is one or more of polyvinyl butyral, polyvinyl formal, nitrile rubber, phenoxy resin, and silicone resin.
[0010] Preferably, the flame retardant is a halogen-free flame retardant or a bromine-containing flame retardant; The halogen-free flame retardant is one or more of phosphazene, phosphate, phosphonate, and diethylaluminum hypophosphite; the bromine-containing flame retardant is one or more of decabromodiphenyl ether, tetrabromobisphenol A, and decabromodiphenyl ethane.
[0011] Preferably, the filler is one or more of aluminum hydroxide, magnesium hydroxide, and silicon powder, and the particle size D50 of the filler is 2-5um, and all of them are surface treated with KH-560.
[0012] Preferably, the solvent A is one or more of acetone, butanone, cyclohexanone, dimethylformamide, ethylene glycol monomethyl ether and propylene glycol monomethyl ether.
[0013] A method for preparing resin glue liquid comprises the following specific steps: firstly, adding phenolic resin, solvent A and flexible material into a glue mixing tank, stirring at 600-1200 rpm for 3-4 hours at a temperature of 10-40°C to dissolve until transparent, then adding epoxy resin and stirring for 1 hour under the same conditions, then adding flame retardant and filler and stirring for 1 hour, stopping stirring, using a ball mill to disperse at a speed of 1000-1500 rpm for 2 times, and then filtering 3 times with a 2000-3000 mesh nylon filter to obtain the resin glue liquid.
[0014] A method for making a filmless flexible copper clad laminate using the prepared resin glue, wherein the filmless flexible copper clad laminate can be divided into a single-sided flexible copper clad laminate and a double-sided flexible copper clad laminate; The production of the single-sided flexible copper-clad laminate specifically includes the following steps: a. selecting a copper foil and applying glue to the rough surface of the copper foil; b. Then, a drying treatment is performed at a temperature of 160-200° C. to obtain a primary single-sided flexible copper clad laminate; c. Measure the glue content and solubility of the primary single-sided flexible copper clad laminate. The glue content that meets the conditions is 15-25g / m2, and the solubility that meets the conditions is 20-30%; d. Finally, the primary single-sided flexible copper clad laminate that has passed the test is cured to obtain a final single-sided flexible copper clad laminate, the curing temperature of which is 170-190° C., and the curing time is 2-4 hours; The production of the double-sided flexible copper clad laminate specifically includes the following steps: a. Select two copper foils and apply glue to the rough surface of one of them; b. Then, a drying treatment is performed at a temperature of 160-200° C. to obtain a primary single-sided flexible copper clad laminate; c. Measure the glue content and solubility of the primary single-sided flexible copper clad laminate. The glue content that meets the conditions is 15-25g / m2, and the solubility that meets the conditions is 20-30%; d. Place the matte surface of another copper foil close to the adhesive surface of the primary single-sided flexible copper clad laminate that has passed the test, and quickly press them together using a roller at a temperature of 70-100°C to obtain a primary double-sided flexible copper clad laminate; e. Finally, the primary double-sided flexible copper clad laminate is cured to obtain the final double-sided flexible copper clad laminate, with a curing temperature of 170-190° C. and a curing time of 2-4 hours.
[0015] Compared with the prior art, the advantages and positive effects of the present invention are: 1. The integrity of the resin glue in the present invention is to finally reflect the self-filming of the cured product, high heat resistance, high bending resistance, and high peel strength; secondly, it is directly coated on the copper foil to finally obtain a flexible copper clad laminate; 2. The flexible copper-clad laminate made of the resin adhesive of the present invention has no film-forming process, reduces costs, improves heat resistance, bending resistance, peeling strength and other indicators, and reduces labor intensity. DETAILED DESCRIPTION
[0016] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0017] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.
[0018] The present invention provides a resin adhesive, a method for preparing the resin adhesive and a method for manufacturing a filmless flexible copper clad laminate using the resin adhesive. The present invention mainly includes three parts: one is the components of the resin adhesive, the second is a method for preparing the resin adhesive using the components, and the third is the application of the resin adhesive in the copper clad laminate. The first and second parts can be explained by a large group of embodiments, and the third part highlights the method for manufacturing a filmless flexible copper clad laminate using the resin adhesive, which is also explained by corresponding embodiments.
[0019] For the resin glue in the present invention, phenolic resin is also very important as a curing agent in the glue system. After curing in the glue system, it can show high heat resistance. Therefore, the inventors independently produced phenolic resin, namely thermosetting phenolic resin, according to the needs.
[0020] For the phenolic resin, 110-130 parts of phenol, 150-160 parts of formaldehyde solution, 15-25 parts of triethylamine and 260-360 parts of solution B (solvent B is a mixture of one or more solvents selected from methanol, ethanol, ethylene glycol monomethyl ether, acetone or butanone), and a preparation method independently designed by the inventor are prepared as follows: a. subjecting a certain mass fraction of phenol, formaldehyde solution and triethylamine to a polymerization reaction treatment, wherein the reaction temperature is 80-100°C and the reaction time is 30-60min; b. Then vacuum dehydration, the processing time is 90-100min, and the dehydration amount is 95-105 parts; c. Add solvent B and cool it down to dissolve, so as to obtain a phenolic resin solution with a solid content of 52-55%, that is, the phenolic resin in the resin glue.
[0021] For the phenolic resin prepared above, different components and variables in the method (time, temperature, etc.) will affect the performance of the phenolic resin, thereby affecting the performance of the resin glue. Therefore, after a large number of experiments, the inventors have obtained the following three grades of phenolic resin (hereinafter assumed to have a solid content of formaldehyde solution of 36%-38%) based on high temperature resistance as the evaluation standard: the first grade, the highest temperature under the premise of maintaining the integrity of its structure and the stability of its size a. 119 parts of phenol, 155 parts of formaldehyde solution and 19 parts of triethylamine were subjected to polymerization reaction at a reaction temperature of 95° C. and a reaction time of 48 min; b. Then vacuum dehydration, the processing time is 95min, and the dehydration amount is 100 parts; c. Add 300 parts of solvent B and cool to dissolve, thereby obtaining a phenolic resin solution with a solid content of 52-55%, i.e., phenolic resin A in the resin glue; The second highest temperature under the premise of maintaining the integrity and dimensional stability of its structure a. 121 parts of phenol, 154 parts of formaldehyde solution and 20 parts of triethylamine were subjected to polymerization reaction at a reaction temperature of 96° C. and a reaction time of 48 min; b. Then vacuum dehydration, the processing time is 95min, and the dehydration amount is 101 parts; c. Add solvent B and cool it down to dissolve, so as to obtain a phenolic resin solution with a solid content of 52-55%, that is, phenolic resin B in the resin glue; The third highest temperature under the premise of maintaining the integrity of its structure and the stability of its size a. 118 parts of phenol, 152 parts of formaldehyde solution and 19 parts of triethylamine were subjected to polymerization reaction at a reaction temperature of 95° C. and a reaction time of 48 min; b. Then vacuum dehydration, the processing time is 95min, and the dehydration amount is 100 parts; c. Add solvent B and cool it down to dissolve, so as to obtain a phenolic resin solution with a solid content of 52-55%, that is, phenolic resin C in the resin glue.
[0022] The high temperature resistant temperatures of the above three phenolic resins and the phenolic resins prepared by the phenolic resin components and methods are as follows: Phenolic resin High temperature resistance (288℃ / S) test method (TMA) Phenolic resin A 600-900 Phenolic resin B 450-600 Phenolic resin C 300-450 Other phenolic resins 120-300 The inventor prepared the above-mentioned phenolic resin (phenolic resin A, B, C) in combination with other components in the resin glue, and obtained phenolic resin B as the optimal item, that is, the resin glue can be raised to a temperature far higher than the high temperature resistance of the existing resin glue (288°C 1800S detection method (TMA measurement T288). Finally, it is supplemented that the inventor also conducted corresponding experiments on the selection of solvent B in phenolic resin. When solvent B is a mixture of ethanol and butanone, it meets all the indicators of phenolic resin B, and the volume ratio of ethanol to butanone is 10:1.
[0023] In the following embodiments, the phenolic resin in the resin glue is assumed to be the phenolic resin B mentioned above; in addition to the selection of the phenolic resin, the components of the resin glue also include epoxy resin, flexible material, flame retardant, filler and solvent A. For the above components, the inventors have concluded through a large number of experiments: The epoxy resin is one or more low molecular weight epoxy resins with an epoxy equivalent of 160-200 g / eq, and the structures of bisphenol A type and bisphenol F type are the best, so bisphenol A type epoxy resin is selected as a component of the resin glue in the following embodiments; Its flexible material is polyvinyl butyral; In view of the current national environment and environmental protection requirements, flame retardants need to meet the requirements of non-volatile and non-corrosive gases during combustion. And flame retardant effect and other issues, so the flame retardant is phosphazene among the halogen-free flame retardants; its solvent A is butanone.
[0024] The characteristics of the present invention are fully illustrated below through two groups of embodiments.
[0025] 1. Comparison of the resin glue and its preparation method in the present invention with the prior art 1. Select 100 parts of phenolic resin, 30 parts of epoxy resin, 80 parts of flexible material, 20 parts of flame retardant, 20 parts of filler, and 500 parts of solvent A, and select the best preparation method, as follows: Example 1
[0026] First, add 100 parts of phenolic resin, 500 parts of solvent A and 80 parts of flexible resin into the glue mixing tank, stir at 600 rpm at 10°C for 3 hours to dissolve until transparent, add 30 parts of epoxy resin and stir for 1 hour under the same conditions, then add 20 parts of flame retardant and 20 parts of filler and stir for 1 hour, stop stirring, use a ball mill to disperse at 1000 rpm for 2 times, and then filter 3 times with a 2000 mesh nylon filter to obtain resin glue A. Example 2
[0027] First, add 100 parts of phenolic resin, 500 parts of solvent A and 80 parts of flexible resin into the glue mixing tank, stir at 900 rpm at 30°C for 3.5 hours until they are dissolved and transparent. Under the same conditions, add 30 parts of epoxy resin and stir for 1 hour. Then add 20 parts of flame retardant and 20 parts of filler and stir for 1 hour. Stop stirring and use a ball mill at 1300 rpm to disperse twice. Filter through a 2500-mesh nylon filter for three times to obtain resin glue solution B. Example 3
[0028] First, add 100 parts of phenolic resin, 500 parts of solvent A and 80 parts of flexible resin into the glue mixing tank, stir at 1200 rpm at 40°C for 4 hours to dissolve until transparent, then add 30 parts of epoxy resin and stir for 1 hour under the same conditions, then add 20 parts of flame retardant and 20 parts of filler and stir for 1 hour, stop stirring, use a ball mill to disperse at 1500 rpm for 2 times, and then filter 3 times with a 3000 mesh nylon filter to obtain resin glue C. Example 4
[0029] First, add 100 parts of phenolic resin, 500 parts of solvent A and 80 parts of flexible resin into the glue mixing tank, stir at 1000 rpm at 25°C for 3.5 hours to dissolve until transparent, then add 30 parts of epoxy resin and stir for 1 hour under the same conditions, then add 20 parts of flame retardant and 20 parts of filler and stir for 1 hour, stop stirring, use a ball mill to disperse at 1400 rpm for 2 times, and then filter through a 2500 mesh nylon filter for 3 times to obtain resin glue D. Example 5
[0030] The existing method obtains the resin glue E.
[0031] Summary: Example 2 is selected as the optimal preparation method, which is used in the preparation of the following resin glue solution, namely: first add phenolic resin, solvent A and flexible resin into the glue mixing tank, stir at 900 rpm at 30°C for 3.5 hours to dissolve until transparent, then add epoxy resin and stir for 1 hour under the same conditions, then add flame retardant and filler and stir for 1 hour, stop stirring, use a ball mill at 1300 rpm to disperse twice, and then filter three times with a 2500 mesh nylon filter to obtain the resin glue solution.
[0032] It is not difficult to see from the above-mentioned Examples 1-5 that Example 2 is the best preparation method. The resin glue obtained by the preparation method is as follows: Example 6
[0033] First, add 100 parts of phenolic resin, 500 parts of solvent A and 80 parts of flexible resin into the glue mixing tank, stir at 900 rpm at 30°C for 3.5 hours to dissolve until transparent, then add 30 parts of epoxy resin and stir for 1 hour under the same conditions, then add 20 parts of flame retardant and 20 parts of filler and stir for 1 hour, stop stirring, use a ball mill to disperse at 1300 rpm for 2 times, and then filter 3 times with a 2500 mesh nylon filter to obtain resin glue F.
[0034] Example 7 First, add 120 parts of phenolic resin, 600 parts of solvent A and 100 parts of flexible resin into the glue mixing tank, stir at 900 rpm at 30°C for 3.5 hours to dissolve until transparent, then add 40 parts of epoxy resin and stir for 1 hour under the same conditions, then add 25 parts of flame retardant and 25 parts of filler and stir for 1 hour, stop stirring, use a ball mill to disperse at 1300 rpm for 2 times, and then filter 3 times with a 2500 mesh nylon filter to obtain resin glue G.
[0035] Example 8 First, add 160 parts of phenolic resin, 800 parts of solvent A and 130 parts of flexible resin into the glue mixing tank, stir at 900 rpm at 30°C for 3.5 hours to dissolve until transparent, then add 50 parts of epoxy resin and stir for 1 hour under the same conditions, then add 30 parts of flame retardant and 30 parts of filler and stir for 1 hour, stop stirring, use a ball mill to disperse at 1300 rpm for 2 times, and then filter 3 times with a 2500 mesh nylon filter to obtain resin glue H. Example 9
[0036] First, add 190 parts of phenolic resin, 1000 parts of solvent A and 150 parts of flexible resin into the glue mixing tank, stir at 900 rpm at 30°C for 3.5 hours to dissolve until transparent, then add 60 parts of epoxy resin and stir for 1 hour under the same conditions, then add 40 parts of flame retardant and 50 parts of filler and stir for 1 hour, stop stirring, use a ball mill to disperse at 1300 rpm for 2 times, and then filter 3 times with a 2500 mesh nylon filter to obtain resin glue solution I.
[0037] Example 10 (without adding phenolic resin) First, add 1000 parts of solvent A and 150 parts of flexible resin into the glue mixing tank, stir at 900 rpm at 30°C for 3.5 hours to dissolve until transparent, then add 60 parts of epoxy resin and stir for 1 hour under the same conditions, then add 40 parts of flame retardant and 50 parts of filler and stir for 1 hour, stop stirring, use a ball mill to disperse at 1300 rpm for 2 times, and then filter through a 2500 mesh nylon filter for 3 times to obtain resin glue J.
[0038] 2. Comparison between the filmless flexible copper clad laminate produced by using resin glue in the present invention and the existing copper clad laminate produced The filmless flexible copper clad laminate was produced by using the resin glue of the best option prepared above.
[0039] Production of single-sided flexible copper clad laminate Example 10
[0040] a. Select a piece of copper foil and apply glue to the rough surface of the copper foil; b. Then, a drying treatment is performed at a temperature of 160° C. to obtain a primary single-sided flexible copper clad laminate; c. Measure the glue content and solubility of the primary single-sided flexible copper clad laminate. The glue content that meets the conditions is 15-25g / m2, and the solubility that meets the conditions is 20-30%; d. Finally, the primary single-sided flexible copper clad laminate that has passed the test is cured to obtain a final single-sided flexible copper clad laminate, with a curing temperature of 170° C. and a curing time of 2 h. Embodiment 11
[0041] a. Select a piece of copper foil and apply glue to the rough surface of the copper foil; b. Then, a drying treatment is performed at a temperature of 180° C. to obtain a primary single-sided flexible copper clad laminate; c. Measure the glue content and solubility of the primary single-sided flexible copper clad laminate. The glue content that meets the conditions is 15-25g / m2, and the solubility that meets the conditions is 20-30%; d. Finally, the primary single-sided flexible copper clad laminate that has passed the test is cured to obtain a final single-sided flexible copper clad laminate, with a curing temperature of 180° C. and a curing time of 3 hours. Example 12
[0042] a. Select a piece of copper foil and apply glue to the rough surface of the copper foil; b. Then, a drying treatment is performed at a temperature of 200° C. to obtain a primary single-sided flexible copper clad laminate; c. Measure the glue content and solubility of the primary single-sided flexible copper clad laminate. The glue content that meets the conditions is 15-25g / m2, and the solubility that meets the conditions is 20-30%; d. Finally, the primary single-sided flexible copper clad laminate that has passed the test is cured to obtain a final single-sided flexible copper clad laminate, with a curing temperature of 190° C. and a curing time of 4 hours.
[0043] Production of double-sided flexible copper clad laminate Embodiment 13
[0044] a. Select two copper foils and apply glue to the rough surface of one of them; b. Then, a drying treatment is performed at a temperature of 160° C. to obtain a primary single-sided flexible copper clad laminate; c. Measure the glue content and solubility of the primary single-sided flexible copper clad laminate. The glue content that meets the conditions is 15-25g / m2, and the solubility that meets the conditions is 20-30%; d. Place the matte surface of another copper foil against the adhesive surface of the primary single-sided flexible copper clad laminate that has passed the test, and quickly press them together using a roller at a temperature of 70°C to obtain a primary double-sided flexible copper clad laminate; e. Finally, the primary double-sided flexible copper clad laminate is cured to obtain a final double-sided flexible copper clad laminate, with a curing temperature of 170° C. and a curing time of 2 h.
[0045] Embodiment 14 a. Select two copper foils and apply glue to the rough surface of one of them; b. Then, a drying treatment is performed at a temperature of 180° C. to obtain a primary single-sided flexible copper clad laminate; c. Measure the glue content and solubility of the primary single-sided flexible copper clad laminate. The glue content that meets the conditions is 15-25g / m2, and the solubility that meets the conditions is 20-30%; d. Place the matte surface of another copper foil close to the adhesive surface of the primary single-sided flexible copper clad laminate that has passed the test, and quickly press them together using a roller at a temperature of 85°C to obtain a primary double-sided flexible copper clad laminate; e. Finally, the primary double-sided flexible copper clad laminate is cured to obtain a final double-sided flexible copper clad laminate, with a curing temperature of 180° C. and a curing time of 3 h.
[0046] Embodiment 15 a. Select two copper foils and apply glue to the rough surface of one of them; b. Then, a drying treatment is performed at a temperature of 200° C. to obtain a primary single-sided flexible copper clad laminate; c. Measure the glue content and solubility of the primary single-sided flexible copper clad laminate. The glue content that meets the conditions is 15-25g / m2, and the solubility that meets the conditions is 20-30%; d. Place the matte surface of another copper foil close to the adhesive surface of the primary single-sided flexible copper clad laminate that has passed the test, and quickly press them together using a roller at a temperature of 100°C to obtain a primary double-sided flexible copper clad laminate; e. Finally, the primary double-sided flexible copper clad laminate is cured to obtain a final double-sided flexible copper clad laminate, with a curing temperature of 190° C. and a curing time of 4 h.
[0047] Comparative Example 1 A method for preparing a flexible copper-clad laminate by pressing, purchasing a PI film with PI glue from Japan, directly covering the copper foil at 180 degrees, pressing at 300 degrees for 6 hours Comparative Example 2 A method for preparing a flexible copper-clad laminate by a coating method, wherein the formula is as follows: 60 parts of bisphenol A type brominated epoxy, 60 parts of nitrile rubber, 20 parts of high-brominated epoxy, 1 part of dicyandiamide, 0.067 parts of 2-methylimidazole, 200 parts of acetone, and 30 parts of silicon micropowder (modified with talc); the preparation method comprises the following steps: weighing each component according to the formula, stirring for 60 minutes, and obtaining a resin adhesive; coating the resin adhesive on a PI film, drying and curing the film, and obtaining a flexible copper-clad laminate; and performing the following tests, as shown in Table 1.
[0048]
[0049] It is obvious that the film-free flexible copper clad laminate prepared by this method has significantly better performance in all aspects than the prior art.
[0050] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the present invention may use the above disclosed technical content to change or modify it into an equivalent implementation with equivalent changes. It is obvious that the film-free flexible copper clad laminate prepared by this method has significantly better performance in all aspects than the prior art.
[0051] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A resin glue, characterized in that: Specifically including by weight: 100-190 parts of phenolic resin; Epoxy resin 30-60 parts; 80-150 parts of flexible materials; Flame retardant 20-40 parts; 20-40 parts of filler; Solvent A 500-1000 parts; The phenolic resin is a thermosetting phenolic resin, which specifically includes, by mass fraction: Phenol 110-130 parts; 150-160 parts of formaldehyde solution; 15-25 parts of triethylamine; Solvent B 260-360 parts; The preparation method of the phenolic resin is: a. subjecting phenol, formaldehyde solution and triethylamine to polymerization reaction at a reaction temperature of 80-100°C and a reaction time of 30-60 minutes; b. Then vacuum dehydration, the processing time is 90-100min, and the dehydration amount is 95-105 parts; c. Adding solvent B to dissolve at reduced temperature to obtain a phenolic resin solution with a solid content of 52-55%, i.e., the phenolic resin in the resin glue; d. The solvent B is a mixture of one or more solvents selected from the group consisting of methanol, ethanol, ethylene glycol monomethyl ether, acetone and butanone.
2. The resin glue according to claim 1, characterized in that: The solid content of the formaldehyde solution is 36%-38%.
3. The resin glue according to claim 1, characterized in that: The epoxy resin is one or more low-molecular epoxy resins with an epoxy equivalent of 160-200 g / eq, and the best structures are bisphenol A type and bisphenol F type.
4. The resin glue according to claim 1, characterized in that: The flexible material is one or more of polyvinyl butyral, polyvinyl formal, nitrile rubber, phenoxy resin and silicone resin.
5. The resin glue according to claim 1, characterized in that: The flame retardant is a halogen-free flame retardant or a bromine-containing flame retardant; the halogen-free flame retardant is one or more of phosphazene, phosphate, phosphonate, and diethyl aluminum hypophosphite; The bromine-containing flame retardant is one or more of decabromodiphenyl ether, tetrabromobisphenol A, and decabromodiphenyl ethane.
6. The resin glue according to claim 1, characterized in that: The filler is one or more of aluminum hydroxide, magnesium hydroxide, and silicon powder, and the particle size D50 of the filler is 2-5 um, and all of them are surface treated with KH-560.
7. The resin glue according to claim 1, characterized in that: The solvent A is one or more of acetone, butanone, cyclohexanone, dimethylformamide, ethylene glycol monomethyl ether and propylene glycol monomethyl ether.
8. A method for preparing the resin glue according to any one of claims 1 to 7, characterized in that: The specific steps are as follows: first add phenolic resin, solvent A and flexible material into the glue mixing tank, stir at 10-40°C and 600-1200rpm for 3-4h to dissolve until transparent, then add epoxy resin and stir for 1h under the same conditions, then add flame retardant and filler and stir for 1h, stop stirring, use a ball mill to disperse at 1000-1500rpm for 2 times, and then filter 3 times with a 2000-3000 mesh nylon filter to obtain the resin glue flexible material.
9. A method for manufacturing a film-free flexible copper-clad laminate using the resin adhesive prepared in claim 8, characterized in that: The film-free flexible copper clad laminate is divided into a single-sided flexible copper clad laminate and a double-sided flexible copper clad laminate; The production of the single-sided flexible copper clad laminate specifically includes the following steps: a. Select a piece of copper foil and apply glue to the rough surface of the copper foil; b. Then, a drying treatment is performed at a temperature of 160-200° C. to obtain a primary single-sided flexible copper clad laminate; c. Measure the glue content and solubility of the primary single-sided flexible copper clad laminate. The glue content that meets the conditions is 15-25g / m 2 , the solubility that meets the conditions is 20-30%; d. Finally, the primary single-sided flexible copper clad laminate that has passed the test is cured to obtain a final single-sided flexible copper clad laminate, the curing temperature of which is 170-190° C., and the curing time is 2-4 hours; The production of the double-sided flexible copper clad laminate specifically includes the following steps: a. Select two copper foils and apply glue to the rough surface of one of them; b. Then, a drying treatment is performed at a temperature of 160-200° C. to obtain a primary single-sided flexible copper clad laminate; c. Measure the glue content and solubility of the primary single-sided flexible copper clad laminate. The glue content that meets the conditions is 15-25g / m2, and the solubility that meets the conditions is 20-30%; d. Place the matte surface of another copper foil close to the adhesive surface of the primary single-sided flexible copper clad laminate that has passed the test, and quickly press them together using a roller at a temperature of 70-100°C to obtain a primary double-sided flexible copper clad laminate; e. Finally, the primary double-sided flexible copper clad laminate is cured to obtain a final double-sided flexible copper clad laminate, with a curing temperature of 170-190° C. and a curing time of 2-4 hours.
Citation Information
Patent Citations
Glue solution for copper-clad plate, composite based CEM-1 copper-clad plate, and preparation methods of glue solution and composite based CEM-1 copper-clad plate
CN106398110A
Metal-based copper clad plate coating adhesive with high thermal conductivity and preparation method thereof
CN110317432A
Environment-friendly glue solution for flexible copper-clad plate and preparation method thereof
CN111234734A
Phenol resin composition and insulating substrate
JP2002060586A
